"Gangnam Style" in Dhaka and inter-Asian refraction. Issue 2 (3rd April 2018) - Yoon, Soo Ryon
ABSTRACT: This essay explores the political implications of the flash mob dance in Dhaka, Bangladesh performed in response to the 2012 global viral sensation of South Korean rapper PSY's "Gangnam Style" music video. The global fame of "Gangnam Style" has much to do with its success online and in the U.S. popular music industry. It, however, also solicited suspicion from popular culture critics that the images of comical PSY worked successfully thanks to unchecked consumption of the racial stereotypes of Asian men. While recognizing these problems as more than valid, this essay simultaneously calls for a more transnational and inter-Asian understanding of the material to argue for a productive quality of PSY's performance. Using "refraction" as a mode of thinking about inter-Asian circulation of pop culture, this essay considers the flash mob performed in Dhaka, Bangladesh as an important yet underexplored case study that shows different performative practices associated with "Gangnam Style" deeply rooted in historicity of colonialism and nationalism. The case study shows that the circulation of "Gangnam Style" materialized through a performance in Dhaka enlarged contemporary discourse among young urban Bangladeshi spectators around Bangladeshiness and its cultural identity. This complicated an easy assumption about "Gangnam Style" and its success in the U.S. mainstream pop culture, while simultaneously displacing the Bangladeshi cultural subjects from the immobile position of "the Other."